Retrospective Genotyping and Whole Genome Sequencing of a Canine Parvovirus Outbreak in Bangladesh - Tofazzal Md Rakib (MDPI AG, 2021)
Canine parvovirus 2 (CPV-2) outbreaks in close quarters such as kennels or shelters can cause substantial case fatality. Thirteen dead Labradors from a secluded kennel of security dogs presented with typical clinical signs and gross pathology of parvovirus infection. Whole genome shotgun sequencing from tissue-extracted genomic DNA detected new CPV-2a as the contributing antigenic variant. Further genotyping using polymerase chain reaction coupled with high-resolution melt assays (PCR-HRM) confirmed new CPV-2a infection in all deceased dogs. PCR-HRM of additional thirty-four clinically suspected dogs suggested that this variant is in wider community circulation, at least in the southeastern part of Bangladesh. We present complete genome sequence of the new CPV-2a variant circulating in the domestic canine population of Bangladesh.